2023
DOI: 10.3390/nano13030476
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Dirac Charge-Density Waves in Bi2Te2Se

Abstract: While parallel segments in the Fermi level contours, often found at the surfaces of topological insulators (TIs), would imply “strong” nesting conditions, the existence of charge-density waves (CDWs)—periodic modulations of the electron density—has not been verified up to now. Here, we report the observation of a CDW at the surface of the TI Bi2Te2Se(111), below ≈350K, by helium-atom scattering and, thus, experimental evidence for a CDW involving Dirac topological electrons. Deviations of the order parameter o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…HAS is ideally suited to study CDW phases since the neutral He beam is directly scattered by the surface electrons and HAS permits determination of the e-ph coupling λ ( Manson et al, 2022 ) which specifies also conventional superconductivity ( Benedek et al, 2020b ). Previous HAS diffraction and phase transition data from HAS are described in Benedek et al (2020b) , including CDW systems with HAS ( Tamtögl et al, 2019 ; Ruckhofer et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…HAS is ideally suited to study CDW phases since the neutral He beam is directly scattered by the surface electrons and HAS permits determination of the e-ph coupling λ ( Manson et al, 2022 ) which specifies also conventional superconductivity ( Benedek et al, 2020b ). Previous HAS diffraction and phase transition data from HAS are described in Benedek et al (2020b) , including CDW systems with HAS ( Tamtögl et al, 2019 ; Ruckhofer et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work [31], we showed that the temperature or incident wave vector dependence of the Debye-Waller (DW) exponent in helium atom scattering (HAS) provides direct information on the total mass enhancement factor λ, characterizing the el-ph interaction at a conducting surface. The value of λ derived in this way (hereafter denoted as λ HAS ) was reported for several metal surfaces [32], overlayers [33], graphene [34], topological semimetals [35][36][37][38], layered dichalcogenides [39,40], 2D superconductors [41] and low-and multi-dimensional surfaces [42].…”
Section: Introductionmentioning
confidence: 97%